2020
DOI: 10.1016/j.celrep.2020.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Activation of Integrin Receptors on Sensory Neurons Induces Allergic Itch

Abstract: Highlights d Periostin induces itch behavior in mice, dogs, and nonhuman primates d Periostin directly activates sensory neurons through its integrin a V b3 receptor d TSLP induces the secretion of periostin in keratinocytes via the JAK/STAT pathway d A TSLP-periostin mutual activation loop might be involved in chronic allergic itch

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 99 publications
2
75
0
Order By: Relevance
“…Cathepsin S, another epidermal cystein protease, is involved in both AD-related inflammation and in histamine-independent itch, by activating Mas-related G-protein-coupled receptors (Mrgprs) and PAR-2 on sensory neurons [20,21]. Furthermore, the multifunctional ECM protein periostin can directly activate primary sensory afferents, via its aVβ3 integrin receptor, in the skin, inducing itch in-vivo, as a pruritogen [22]. Periostin release from keratinocytes and fibroblasts is further stimulated by TSLP and other canonical Th2-cytokines (IL-4, IL-13) in a paracrine fashion, in a vicious cycle feedback loop, as discussed in the next section [23].…”
Section: Th2 Immunity As a Driver Of Chronic Pruritusmentioning
confidence: 99%
“…Cathepsin S, another epidermal cystein protease, is involved in both AD-related inflammation and in histamine-independent itch, by activating Mas-related G-protein-coupled receptors (Mrgprs) and PAR-2 on sensory neurons [20,21]. Furthermore, the multifunctional ECM protein periostin can directly activate primary sensory afferents, via its aVβ3 integrin receptor, in the skin, inducing itch in-vivo, as a pruritogen [22]. Periostin release from keratinocytes and fibroblasts is further stimulated by TSLP and other canonical Th2-cytokines (IL-4, IL-13) in a paracrine fashion, in a vicious cycle feedback loop, as discussed in the next section [23].…”
Section: Th2 Immunity As a Driver Of Chronic Pruritusmentioning
confidence: 99%
“…Lumbar DRGs were isolated from naïve, control, and MIA-injected mice, sectioned on a cryostat at 12 μm thickness for double immunofluorescence labeling (46). Primary antibodies were diluted (1:500 each) in 5% blocking solution.…”
Section: Methodsmentioning
confidence: 99%
“…Because periostin induces TSLP secretion by keratinocytes, an amplification loop involving periostin and TSLP is considered to be a mechanism of the dermal remodeling and epidermal hyperplasia typical of chronic AD 45,105,106 . Recently, it was demonstrated that periostin induced itch in mice, dogs and monkeys and the integrin aVb3 was identified as the periostin neuronal receptor 94 . In addition, given that keratinocytes release periostin in response to TSLP, it was found that an amplification loop involving periostin and TSLP may also be involved in chronic allergic itch 94 …”
Section: Intense Itch In Admentioning
confidence: 99%
“…45,105,106 Recently, it was demonstrated that periostin induced itch in mice, dogs and monkeys and the integrin aVb3 was identified as the periostin neuronal receptor. 94 In addition, given that keratinocytes release periostin in response to TSLP, it was found that an amplification loop involving periostin and TSLP may also be involved in chronic allergic itch. 94…”
Section: Periostinmentioning
confidence: 99%
See 1 more Smart Citation